2009
DOI: 10.1039/b816965a
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the effect of amino acids on an integrated mTOR and insulin signaling pathway

Abstract: Integration of nutrient and growth factor signaling pathways through mammalian TOR (mTOR) plays a central role in the regulation of cell growth. However, the mechanism of integration of these two signals in mTOR activation is largely unknown. Moreover, the nutritional input involving amino acids is yet to be characterized. Excess amino acid conditions, such as in obesity and protein-rich diets, are known to regulate insulin signaling through mTOR activation resulting in insulin resistance. Here, we develop a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 84 publications
0
38
0
Order By: Relevance
“…There are several other systems modelling studies of the mTOR network (for example, Jain and Bhalla, 2009; ref. 41), but only one has attempted to model multiple aa inputs42 and found that a single input via mTORC1 was sufficient to explain a set of reported observations. Using time-course data only, our computational strategy for exploring alternative aa inputs allowed us to comprehensively cover model structures that showed an improvement to the canonical single aa-mTORC1 input.…”
Section: Discussionmentioning
confidence: 99%
“…There are several other systems modelling studies of the mTOR network (for example, Jain and Bhalla, 2009; ref. 41), but only one has attempted to model multiple aa inputs42 and found that a single input via mTORC1 was sufficient to explain a set of reported observations. Using time-course data only, our computational strategy for exploring alternative aa inputs allowed us to comprehensively cover model structures that showed an improvement to the canonical single aa-mTORC1 input.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although AA availability is the main limiting factor for milk protein synthesis (Bequette et al, 1998), the production of milk protein has also been shown to dramatically increase through endocrine signals only (McGuire et al, 1995;Griinari et al, 1997;Mackle et al, 2000). However, AA supply together with endocrine signals prompted by glucogenic nutrients seem to be highly interconnected in pathways involved in milk protein synthesis (Burgos et al, 2010;Bionaz and Loor, 2011), and some interactions between these stimuli have been previously documented at the molecular level (Vinod and Venkatesh, 2009;Burgos et al, 2010;Rius et al, 2010). Hence, a need to assess the effect of CHO on mammary metabolism at different protein intakes levels exists.…”
Section: Introductionmentioning
confidence: 92%
“…However, the lack of time-resolved data is problematic since the authors claim that they describe the dynamics of the insulin signaling network. Despite the shortcomings of the Sedaghat model, it has been extensively used and also further developed [143][144][145] and analyzed [146]. Recently, another more theoretical attempt at constructing a detailed model of insulin signaling was published [141].…”
Section: Detailed Mathematical Models Of the Insulin Signaling Networkmentioning
confidence: 99%